The Rid family member RutC of Escherichia coli is a 3-aminoacrylate deaminase - Buckner, Brandi A.; Lato, Ashley M.; Campagna, Shawn R.; Downs, Diana M. (The Journal of biological chemistry, 2021)
The Rid protein family (PF14588, IPR006175) is divided into nine subfamilies, of which only the RidA subfamily has been characterized biochemically. RutC, the founding member of one subfamily, is encoded in the pyrimidine utilization (rut) operon that encodes a pathway that allows Escherichia coli to use uracil as a sole nitrogen source. Results reported herein demonstrate that RutC has 3-aminoacrylate deaminase activity and facilitates one of the reactions previously presumed to occur spontaneously in vivo. RutC was active with several enamine–imine substrates, showing similarities and differences in substrate specificity with the canonical member of the Rid superfamily, Salmonella enterica RidA. Under standard laboratory conditions, a Rut pathway lacking RutC generates sufficient nitrogen from uracil for growth of E. coli. These results support a revised model of the Rut pathway and provide evidence that Rid proteins may modulate metabolic fitness, rather than catalyzing essential functions.